HIV prevalence and predictors among rescued sex-trafficked women and girls in Mumbai, India. - Silverman, Jay G; Decker, Michele R; Gupta, Jhumka; Maheshwari, Ayonija; Patel, Vipul; Raj, Anita (Journal of acquired immune deficiency syndromes (1999), 2006)
Despite the rapid spread of India's HIV epidemic through commercial sex and the large numbers of minor girls trafficked to India for sex work each year, little HIV research has been conducted among victims of sex trafficking. The present study examines the prevalence and predictors of HIV infection among sex-trafficked women and girls rescued from brothels in Mumbai, India.
Keywords: Adolescent; Adult; Child; Female; HIV Infections; Humans; India; Odds Ratio; Prevalence; Prostitution